2017
DOI: 10.9744/ced.19.2.63-72
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Skills for Managing Construction Safety

Abstract: Previous research has suggested that self-awareness, visioning, and sincerity are foundational managerial skills for delivering positive safety outcomes in construction projects. This paper aims to verify this finding and to suggest learning approaches for developing these skills in practice. Interviews with experienced construction practitioners were analysed thematically to find common themes. The thematic analysis confirms the necessity of the managerial skills identified in the previous research for managi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The project management team is responsible for developing a practical safety plan, allocating adequate resources, monitoring and assessing site safety conditions, initiating and attending regular safety meetings and training, and coordinating all project stakeholders to ensure their active involvement in managing safety (Mohurd and Aqsiq, 2011a). Due to the high level of risk and complex multistakeholder environments in subway construction projects, the project management team's capabilities, experience and accountability is likely to have a more significant impact on safety management performance (Sunindijo et al , 2017). Therefore, selecting project management team members with the right skill profile is a key success factor to influence safety.…”
Section: Discussionmentioning
confidence: 99%
“…The project management team is responsible for developing a practical safety plan, allocating adequate resources, monitoring and assessing site safety conditions, initiating and attending regular safety meetings and training, and coordinating all project stakeholders to ensure their active involvement in managing safety (Mohurd and Aqsiq, 2011a). Due to the high level of risk and complex multistakeholder environments in subway construction projects, the project management team's capabilities, experience and accountability is likely to have a more significant impact on safety management performance (Sunindijo et al , 2017). Therefore, selecting project management team members with the right skill profile is a key success factor to influence safety.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this result argues that construction project manager competencies in the contracting companies working in Gaza Strip ultimately influence the employees' safety performance by influencing the reported accidents & work injuries in work site. In this line, Sunindijo et al (2017) revealed that construction industry has a reputation as being one of the most dangerous industrial sectors, with accident, injuries and fatality rates being constantly much higher than the all-industry average.…”
Section: Respondent's Informationmentioning
confidence: 99%
“…Additionally, it entails investing social exchange constructs in a safety context, in a bid to increase an understanding of elements integral in influencing safety perceptions and behaviour (Hofmann et al, 2003). Indeed, the studies focussing on safety leadership and supervision help stakeholders be aware of the potential of PCS theory and the effect it has on construction safety studies (Love et al, 2018;Gunduz and Ahsan, 2018;Sunindijo et al, 2017;Hofmann et al, 2017;Zohar, 2010). The simultaneous focus on both parties that play a role in contributing to occupational safety context is innovative and offers another option to the traditional approach used in safety evaluation (Zohar, 2010).…”
Section: Implications For Construction Researchersmentioning
confidence: 99%
“…Despite top-level managers aiming for zero accidents, safety performance studies from (Sanni-Anibire et al, 2020) acknowledge that the construction industry is one of the most hazardous industries when compared to other labour-intensive industries (Gunduz and Ahsan, 2018;Xia et al, 2018;Sunindijo et al, 2017). Based on accidents, deaths and injuries, global statistical data ranks the construction industry in the top ten.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation